EDUKASI BAHAYA PENGGUNAAN GADGET YANG BERLEBIHAN PADA SISWA SMK 2 PEKANBARU - Afifah Cahayani Adha; Asep Marzuki; Sisi Hendriani (LPPM Universitas Awal Bros, 2024)
The aim of this educational activity is on the dangers of excessive use of gadgets among students at Vocational High School (SMK) 2 Pekanbaru so that participants can understand the impacts of excessive use of gadgets, both physically, psychologically and socio-economically. Socialization activities use participatory methods, lectures and discussions. The socialization activity was carried out on May 20 2024 with the number of participants taking part in the socialization activity consisting of 40 students located in classes at Vocational High School (SMK) 2 Pekanbaru. For this reason, through educational activities on the dangers of excessive use of gadgets among students, it is possible to increase the understanding of students at Vocational High School (SMK) 2 Pekanbaru regarding the dangers of excessive use of gadgets, the impact of including gadgets from physical, psychological, educational, social and economic aspects as well as How to prevent excessive use of gadgets among children and teenagers. For this reason, this socialization activity can protect the younger generation as the nation's next generation, especially students at Vocational High School (SMK) 2 Pekanbaru from the dangers of using gadgets.